Disease influences male advertisement and mating outcomes in a critically endangered amphibian. (March 2021) - Kelleher, Shannon R.; Scheele, Ben C.; Silla, Aimee J.; Keogh, J. Scott; Hunter, David A.; Endler, John A.; Byrne, Phillip G.
Abstract : The sublethal effects of infectious disease on reproductive behaviour and mating success are not well understood. Here, we investigated predictors of male mating success in one of Australia's most critically endangered vertebrates: the northern corroboree frog, Pseudophryne pengilleyi . Using a genomic approach to assign parentage, we explored whether infection with the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ), a pathogen responsible for amphibian declines globally, influenced male calling behaviour and mating success. We also explored whether male mating success was predicted by phenotypic traits (age, body size, coloration, call characters) that potentially signal genetic quality, and the soil moisture (water potential) of male-constructed terrestrial nests, which may directly impact offspring survival. We found that Bd significantly influenced male advertisement; Bd -infected males produced calls with significantly higher pulse repetition rates than uninfected males. Older males had a higher probability of mating; however, variation in the number of eggs in a nest was most strongly explained by an interaction between male Bd infection status and call pulse repetition rate. We propose that these relationships may result from either pathogen-mediated changes to host behaviour or host-mediated changes to behaviour (e.g. terminal investment). Regardless of the mechanism, this is the first evidence that male mating success in an amphibian can be influenced by male Bd infection status, highlighting a novel mechanism through which this virulent pathogen can affect amphibian fitness. More broadly, these findings add to a growing body of evidence that pathogens can alter the reproductive biology of their hosts. From a conservation perspective, increased consideration of how sexual selection operates in altered environments has the potential to assist with the management of threatened amphibians worldwide. Highlights: We studied the effect of chytrid infection on male mating success in corroboree frogs. Chytrid infection influenced male calling and the number of eggs in a male's nest. Male age also influenced mating success. We show for the first time that disease can alter amphibian mating outcomes.